2013
DOI: 10.1021/ac3035629
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Membrane Neutral Phenol-Sensitive Electrodes for Potentiometric G-Quadruplex/Hemin DNAzyme-Based Biosensing

Abstract: ABSTRACT:The first potentiometric transducer for Gquadruplex/hemin DNAzyme-based biosensing has been developed by using potential responses of electrically neutral oligomeric phenols on polymeric membrane electrodes. In the presence of G-quadruplex/hemin DNAzyme and H 2 O 2 , monomeric phenols (e.g., phenol, methylphenols, and methoxyphenols) can be condensed into oligomeric phenols. Because both substrates and products are nonionic under optimal pH conditions, these reactions are traditionally not considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…This result is expected since the two samples have similar peak molecular weights and wt.% sulfate, and indicates that polyphenols and other components often found in nutritional grade extracts from macroalgae do not affect sensor performance (one would expect polyphenols to be neutral at pH 7.4). Wang et al recently reported that TDMA-doped polymeric membrane electrodes were capable of responding to neutral phenols [49]. However, the minimum detection limit for polyphenols in that work was much higher than the polyphenol concentration in any of the fucoidan preparations studied here (all fucoidan preparations contained <2 m/m% polyphenol).…”
Section: Non-equilibrium Fucoidan Detectionmentioning
confidence: 56%
“…This result is expected since the two samples have similar peak molecular weights and wt.% sulfate, and indicates that polyphenols and other components often found in nutritional grade extracts from macroalgae do not affect sensor performance (one would expect polyphenols to be neutral at pH 7.4). Wang et al recently reported that TDMA-doped polymeric membrane electrodes were capable of responding to neutral phenols [49]. However, the minimum detection limit for polyphenols in that work was much higher than the polyphenol concentration in any of the fucoidan preparations studied here (all fucoidan preparations contained <2 m/m% polyphenol).…”
Section: Non-equilibrium Fucoidan Detectionmentioning
confidence: 56%
“…31 Membrane components of 344 mg were dissolved in 4 mL THF solution. The membrane mixture were then transferred to a glass ring (5.0 cm i.d.)…”
Section: Electrode Preparationmentioning
confidence: 99%
“…These unexpected anionic responses can be explained by the net movement of hydrogen ions from the membrane phase to the aqueous phase 70 stimulated by neutral phenols. 28,32,33 Inspired by these findings, we explored the application of the nonclassical response in the BPS determination. In order to guarantee that BPS exists mostly in its neutral form, 30 mM phosphate buffer solution (PBS) with a pH of 5.0 was used as the background solution.…”
mentioning
confidence: 99%